The synergy between climate change policies and national development goals: Implications for sustainability. (10th March 2020) - Hasan, Md Arif; Abubakar, Ismaila Rimi; Rahman, Syed Masiur; Aina, Yusuf A.; Islam Chowdhury, Md Monirul; Khondaker, A.N.
Abstract: Climate change mitigation in rapidly growing developing countries is receiving increased global attention, especially after the 2016 Paris Agreement. In Bangladesh, the government has initiated some climate change policies to reduce its greenhouse gas emissions in the last decade. However, the rate of emissions has been increasing recently, which questions the emissions reduction potential of these policies. Therefore, this study has utilized relevant indicators to evaluate the extent to which the policies are mitigating climate change, and of their synergy with national development goals. The findings indicate that the policies have limited impacts on energy decarbonization, energy demand management, and emissions sink improvement. Although policies on renewable energy, energy efficiency and demand management, and afforestation are aligned with national development goals, the policies on electricity generation from coal and forest biomass have little synergy with the goals. By quantitatively evaluating the effects of its climate change policies in enhancing socioeconomic, and environmental benefits, this study can assist Bangladesh's policymakers to understand the impact of the policies on climate change mitigation and their level of integration with national development goals. Also, other developing countries can adopt the study methodology to evaluate their climate change policies and track their progress. Graphical abstract: Image 10614 Highlights: Customized indicators were used to evaluate the effects of climate policies. Bangladesh's energy efficiency measures have achieved some success in recent years. Decarbonization, energy demand management and carbon sink options are inadequate. Increased use of coal and biomass hinders achieving the national development goals. Renewables and afforestation programs have synergy with national development goals.